Experimental induction of reparative morphogenesis and adaptive reserves in the ischemic myocardium using multipotent mesenchymal bone marrow-derived stem cells. Issue 2 (June 2016) - Mykhaylichenko, V.Yu.; Kubyshkin, A.V.; Samarin, S.A.; Fomochkina, I.I.; Anisimova, L.V.
Abstract: Introduction: Current experimental research has proven the efficacy of transplantation bone marrow-derived mesenchymal stem cells (MSC) in the treatment of myocardial infarction (MI). The one of the main purposes of research was to evaluate the comparative data of the MSC transplantation with (5-azacytidine) and without commitment and to assess the post transplantation effects. Methods: The efficiency of intravenous cardiomyoplasty by infusion of MSC was evaluated in female Wistar-Kyoto rats with myocardial infarction model using echocardiography, morphological study, morphometry, immunohistostaining, data from in situ hybridization, and by measurement of blood serum levels of nitric oxide, endothelin-1, vascular endothelial growth factor (VEGF), and fibroblast growth factor 2 (FGF2). Results: The transplanted MSC were detected in all layers of the myocardium; MCS actively participate in the formation of blood vessels and connective tissue in the scar zone. There was no observable differentiation of male MSC into cardiomyocytes in female rats with MI. However, MSC transplantation leads to significant improvement in vascularization in the area of MI, elevation blood serum levels of nitric oxide, VEGF, and FGF2. No significant differences were identified morphologically between the two groups of animals after transplantation with unmodified MSC or commited MSC (5-azaC). Conclusion: Intravenous transplantation of MSC without commitment in rats with MI improves the contractile function of the heart, the morphology of the myocardium, and should be recommended for further clinical investigation as an alternative approach to deal with heart diseases.